Learn more about

Refine search

Results (displaying all 40 matches)

Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
464.a.29696.1 464.a \(y^2 + (x + 1)y = 8x^5 + 3x^4 - 4x^3 - 2x^2\) $\mathrm{USp}(4)$ 0
472.a.944.1 472.a \(y^2 + (x^2 + 1)y = x^5 - x^4 - 2x^3 + x\) $\mathrm{USp}(4)$ 0
504.a.27216.1 504.a \(y^2 + (x^3 + x)y = 3x^4 + 15x^2 + 21\) $G_{3,3}$ 0
576.b.147456.1 576.b \(y^2 = x^6 + 2x^4 + 2x^2 + 1\) $E_1$ 0
600.b.30000.1 600.b \(y^2 + (x^3 + x)y = x^4 + x^2 - 3\) $G_{3,3}$ 0
630.a.34020.1 630.a \(y^2 + (x^2 + x)y = 3x^5 + 10x^4 - 23x^2 - 6x + 15\) $G_{3,3}$ 0
741.a.28899.1 741.a \(y^2 + (x + 1)y = -3x^5 - x^4 + 2x^2 + x\) $\mathrm{USp}(4)$ 0
830.a.6640.1 830.a \(y^2 + (x^3 + 1)y = -x^5 + x^4 - 2x^2 + x + 1\) $\mathrm{USp}(4)$ 0
830.a.830000.1 830.a \(y^2 + (x^2 + x)y = x^5 - 2x^4 + 16x^3 + 8x^2 + x\) $\mathrm{USp}(4)$ 0
862.a.6896.1 862.a \(y^2 + (x^2 + x)y = 4x^5 + 6x^4 - 3x^2 - x\) $\mathrm{USp}(4)$ 0
882.a.63504.1 882.a \(y^2 + (x^2 + x)y = x^5 + x^4 + x^3 + 3x^2 + 3x + 1\) $G_{3,3}$ 0
909.a.8181.1 909.a \(y^2 + xy = 3x^5 - 7x^4 + x^3 + 6x^2 - 3x\) $\mathrm{USp}(4)$ 0
925.a.23125.1 925.a \(y^2 + xy = 5x^5 + x^4 - 19x^3 + 18x^2 - 5x\) $\mathrm{USp}(4)$ 0
1008.a.27216.1 1008.a \(y^2 + (x^3 + x)y = -4x^4 + 15x^2 - 21\) $G_{3,3}$ 0
1184.a.606208.1 1184.a \(y^2 = 2x^5 + x^4 - 8x^3 - 8x^2 - 2x\) $\mathrm{USp}(4)$ 0
1200.a.30000.1 1200.a \(y^2 + (x^3 + x)y = -2x^4 + x^2 + 3\) $G_{3,3}$ 0
1200.a.450000.1 1200.a \(y^2 + (x^3 + x)y = 4x^4 + 25x^2 + 45\) $G_{3,3}$ 0
1311.a.814131.1 1311.a \(y^2 + xy = x^5 + 5x^4 + 5x^3 + 4x^2 + x\) $\mathrm{USp}(4)$ 0
1408.b.180224.2 1408.b \(y^2 = 2x^5 - 4x^3 - x^2 + 2x + 1\) $\mathrm{USp}(4)$ 0
1524.a.780288.1 1524.a \(y^2 + (x^3 + x^2 + x)y = 2x^4 + 4x^3 + 8x^2 + 6x + 4\) $\mathrm{USp}(4)$ 0
1536.b.49152.1 1536.b \(y^2 + x^3y = -3x^4 + 11x^2 - 12\) $N(G_{1,3})$ 0
1624.a.831488.1 1624.a \(y^2 + (x^3 + x)y = x^5 + 2x^3 + 2x^2 + x + 1\) $\mathrm{USp}(4)$ 0
1734.b.41616.1 1734.b \(y^2 + (x^2 + x)y = x^6 - 3x^5 - x^4 + 6x^3 - 4x - 1\) $G_{3,3}$ 0
1832.b.14656.1 1832.b \(y^2 + (x + 1)y = 2x^5 - 4x^3 - 2x^2\) $\mathrm{USp}(4)$ 0
2121.a.400869.1 2121.a \(y^2 + xy = x^5 - 2x^4 - 4x^3 + 8x^2 - 1\) $\mathrm{USp}(4)$ 0
2154.a.465264.1 2154.a \(y^2 + (x^2 + x)y = x^5 - 9x^3 - x^2 + 18x - 1\) $\mathrm{USp}(4)$ 0
2288.a.805376.1 2288.a \(y^2 + (x + 1)y = -4x^5 - x^4 - x^3 - x^2\) $\mathrm{USp}(4)$ 0
2520.a.408240.1 2520.a \(y^2 + (x^2 + 1)y = 5x^6 - 23x^4 + 33x^2 - 16\) $G_{3,3}$ 0
2604.a.62496.1 2604.a \(y^2 + (x^2 + x)y = -2x^5 - 14x^4 + 77x^2 - 93x + 31\) $G_{3,3}$ 0
2940.b.752640.1 2940.b \(y^2 + (x^2 + x)y = x^6 + x^5 + 3x^4 + x^3 + 3x^2 + x + 1\) $G_{3,3}$ 0
3320.a.132800.1 3320.a \(y^2 + (x + 1)y = -2x^5 - 2x^4\) $\mathrm{USp}(4)$ 0
3336.c.80064.1 3336.c \(y^2 + (x + 1)y = 6x^5 + 2x^4 + 2x^2 + x\) $\mathrm{USp}(4)$ 0
3528.c.592704.1 3528.c \(y^2 + (x^3 + x)y = x^3 - 2x^2 + 3x - 3\) $G_{3,3}$ 0
3978.a.930852.1 3978.a \(y^2 + (x^2 + x)y = x^5 + 3x^4 - 3x^3 - 8x^2 + 6x\) $\mathrm{USp}(4)$ 0
4950.a.742500.1 4950.a \(y^2 + (x^2 + x)y = 15x^5 - 22x^3 - 5x^2 + 8x + 3\) $G_{3,3}$ 0
5040.c.141120.1 5040.c \(y^2 + (x^3 + x)y = -x^6 - 36x^4 - 560x^2 - 2940\) $G_{3,3}$ 0
5680.a.908800.1 5680.a \(y^2 + (x + 1)y = 4x^5 + 7x^4 - 3x^3 - 3x^2\) $\mathrm{USp}(4)$ 0
6120.b.440640.1 6120.b \(y^2 + (x + 1)y = 2x^5 + 2x^4 - 6x^3 + x\) $\mathrm{USp}(4)$ 0
7205.a.396275.1 7205.a \(y^2 + (x + 1)y = 5x^5 + x^4 + 6x^2 + 2x\) $\mathrm{USp}(4)$ 1
14904.c.804816.1 14904.c \(y^2 + (x + 1)y = 6x^5 + 6x^4 - 3x^3 - 3x^2\) $\mathrm{USp}(4)$ 0


Download all search results for